Experimental and numerical study on mechanical behavior of hybrid multi-cell structures under multi-crushing loads. (January 2022) - Xiong, Jun; Zhang, Yong; Su, Liang; Zhang, Feng; Wu, Changfeng
Abstract: Thin-walled multi-cell structures are the most typical protective structures owing to their excellent energy absorption characteristics. Hybrid multi-cell structures (HMSs), a combination of circular and polygonal cross sections, are proposed to take crashworthiness advantage of different cross-section thin-walled structures. Their mechanical behaviors under multi-crushing loads are investigated experimentally and numerically. The experimental results show that the HMS can experience stable folding deformation and effectively absorb energy under 10° oblique load. Furthermore, the numerical analysis finds that the load curves of HMSs with outer circular section have a more stable plateau stage than those of structures with outer polygonal section. In addition, the connecting position of ribs also has an important effect on the force and displacement response of the HMS. Therefore, the comprehensive crashworthiness of HMSs under multi-crushing loads is further evaluated by the grey relation analysis (GRA). The HMS consisted of the circular and hexagonal section is an optimal hybrid scheme. Furthermore, the hybrid structure that ribs connect the outer circular section and the midpoint of the inner hexagon's edge (CHM) exhibits the best crashworthiness. Then, the crashworthiness of a bumper system with the CHM is further investigated to reveal the protective performance of the hybrid multi-cell design under frontal and oblique impact conditions. The results show that the protective performance of the CHM bumper system is better than that of the original bumper system. This study provides a highly efficient and low-cost design method to improve the energy absorption of the protective structures. Highlights: Hybrid multi-cell structures are proposed to design a high effective energy absorber. The hybrid way and load angle have significant effect on energy absorption. The CHM has the best comprehensive crashworthiness under multi impacting loads. The protective performance of the CHM bumper system is better than that of the original bumper system.